Heading Through a Crowd. (September 2018) - Riddell, Hugh; Lappe, Markus
The ability to navigate through crowds of moving people accurately, efficiently, and without causing collisions is essential for our day-to-day lives. Vision provides key information about one's own self-motion as well as the motions of other people in the crowd. These two types of information (optic flow and biological motion) have each been investigated extensively; however, surprisingly little research has been dedicated to investigating how they are processed when presented concurrently. Here, we showed that patterns of biological motion have a negative impact on visual-heading estimation when people within the crowd move their limbs but do not move through the scene. Conversely, limb motion facilitates heading estimation when walkers move independently through the scene. Interestingly, this facilitation occurs for crowds containing both regular and perturbed depictions of humans, suggesting that it is likely caused by low-level motion cues inherent in the biological motion of other people.